Nutrient Salts and Chlorophyll-a During Short Term Scale in the Eastern Harbor, Alexandria (Egypt). - H.M, Faragallah; H.R.Z, Tadros; M.A., Okbah (Malaysian Journal of Science, 2010)
The present study aims to follow the changes of NH4-N, NO2 -N, NO3-N, PO4-P, SiO4, chlorophyll-a (Chl-a), OOM and pH-values in a rapid short-term variation. During the period from August 2004 - 2005, 136 surface water samples were collected three times every week from the Eastern Harbor, Alexandria (Egypt). The study revealed that the pH values lie in alkaline side, with a range of (7.53-8.70), Chl-a showed a wide range (0.41-78.68g/l) with an average value of 13.60 g/l. The range and the average obtained values of nutrients (Â¼mole/l) were; 0.47-10.40(2.23) for NO3-N, 0.12-1.48 (4.06) for NO2 -N, 0.35-6.19(2.23) for NH4-N, 0.04-8.58(1.03) for PO4-P, and 0.37-11.90(3.45) for SiO4. The values of OOM ranged from 0.42 to 17.50 mg O2/l with an average value of 4.73mg/L. The distribution of both NO3-N and NH4-N were referred to that the rate of nitrification and denitrification is mostly similar. The N/P ratio (4.76) in the present study is lower than Redfield's ratio , indicated that nitrogen is the limiting factor. The levels of nutriens and chlorophyll-a indicated that the harbor is in eutrophic condition.